Improved exponential estimator for population variance using two auxiliary variables - Singh, Rajesh; Chauhan, Pankaj; Sawan, Nirmala; Smarandache, Florentin (Italian Journal of Pure and Applied Mathematics, 2011)
In this paper, exponential ratio and exponential product type estimators using two auxiliary variables are proposed for estimating unknown population variance S2y. Problem is extended to the case of two-phase sampling. Theoretical results are supported by an empirical study.